2020
DOI: 10.1039/d0ra02868a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of flower-like hierarchical N-doped Nb2O5/C nanostructures with efficient photocatalytic activity under visible light

Abstract: Flower-like hierarchical N-doped Nb2O5/C nanostructures with efficient visible light-driven photocatalytic activity synthesized via a facile hexamethylenetetramine-assisted hydrothermal route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…As illustrated in Fig. 4(a), the typical absorption borders of OCN and pure CN are around 520 and 470 nm, respectively, whereas pure Nb2O5 only exhibits UV light absorption properties, as previously reported [19]. Remarkably, all the OCN-[N-NBO/C] samples, including the 1OCN-[N-NBO/C], which contain a low amount of OCN, display enhanced light absorption performances than Pure Nb2O5.…”
Section: Construction Confirmationsupporting
confidence: 79%
See 2 more Smart Citations
“…As illustrated in Fig. 4(a), the typical absorption borders of OCN and pure CN are around 520 and 470 nm, respectively, whereas pure Nb2O5 only exhibits UV light absorption properties, as previously reported [19]. Remarkably, all the OCN-[N-NBO/C] samples, including the 1OCN-[N-NBO/C], which contain a low amount of OCN, display enhanced light absorption performances than Pure Nb2O5.…”
Section: Construction Confirmationsupporting
confidence: 79%
“…The nanostructured flower-like hierarchical N-NBO/C was fabricated through a mild hydrothermal route similar to that reported in our previous work [19]. Initially, 2 mmol of C10H5NbO20•xH2O was dissolved in a solution containing 15 mL DW and 10 mL of ethanol and named solution A.…”
Section: Fabrication Of 3d N-nbo/c Nanoflowersmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, it is reported that hydrothermal treatment of niobium oxide produces a variety of crystal structures. [19][20][21] Therefore, the niobium oxides and their hydrates with a lower oxidation number were formed in a primal synthesis step. A weak peak at 22.6°was attributed to (001) peak estimated from lattice parameters of Nb 2 O 5 (a ¼ 6.209, b ¼ 28.999, c ¼ 3.923, Pbam, CCDC#2 103 847).…”
Section: Resultsmentioning
confidence: 99%
“…17), and 3D flower-like hierarchical nitrogen-doped and carbonsensitized Nb 2 O 5 (N-NBO/C) nanostructures have been fabricated for solar energy transformation and environmental remediation (Fig. 18) [84,85]. Despite this, the structural control over a larger scale range, mechanical properties of the selfassembly materials, the combination of different molecules into advances have been achieved, as it is still in the early stages, several important issues, such as limited resolution, low throughput, high cost, limited flexibility in material choice, and 3D structure shape, still remain.…”
Section: Bottom-up Techniquesmentioning
confidence: 99%